Contact toxicity of the crude extract of Chinese star anise fruits to house fly larvae and their development - Guntharee Sripongpun (Songklanakarin Journal of Science and Technology (SJST), 2008)
Contact toxicity of the ethanol crude extract of Chinese star anise fruits, Illicium verum Hook. F. (Illiciaceae) to house fly larvae, Musca domestica L. (Diptera: Muscidae) and their development were determined by a dipping method. Younger larvae were more susceptible than older. The median lethal concentration (LC50) values of the crude extract to the 2nd instar larvae at 24, 48 and 72 hours were 7.4x104, 4.1x104 and 3.2x104 mg/l, respectively. Furthermore, treated extractsaffected house fly development in pupal and adult stages. The number of test larvae developed to pupae and adults was lessthan that of control group. The crude extract at concentration 8.5x104 mg/l completely inhibited development from larvae to pupae. In addition, small pupae were found at every concentration between 2.5x103 -105x103 mg/l. Small treated pupae were observed more at higher concentrations. Some of them could continually develop to adults but their developmental percentageswere less than those of normal sized pupae in treatments and in control group. The crude extract of Chinese star anise fruits can be applied as an optional point source control of house fly.